Capacity Choice under Uncertainty with Product Differentiation - Christiaan Behrens; Mark Lijesen (Tinbergen Institute, 2012)
This article analyses the capacity-then-price game for a duopoly market. We add to the literature by explicitly taking product differentiation into account. We study the impact of capacity costs, demand uncertainty, and vertical and horizontal product differentiation on equilibrium capacities, efficiency, and price dispersion. We identify a minimum degree of vertical product differentiation, relative to horizontal product differentiation, for which the subgame perfect Nash equilibrium in pure strategies is guaranteed to exist. We find that if firms' quality differences exactly offset cost differences, asymmetric outcomes in the capacity stage arise, with the low-cost, low-quality firm providing more capacity than its competitor. We show that the highest level of efficiency is reached at the degree of vertical product differentiation where it would be optimal for welfare if firms had equal capacities. Furthermore, our model provides an explanation for ambiguous results in empirical research on price dispersion.
urn:NBN:nl:ui:31-1871/39439
Keywords: D43; L11; L13; 330; Price competition; Capacity choice; Demand uncertainty; Product differentiation; Price dispersion; Produktdifferenzierung; Konsumentenverhalten; Kapazitätsplanung; Entscheidung bei Unsicherheit; Duopol; Theorie